THE USE OF COHESIVE DEVICES IN WRITING ENGLISH TEXT BY THE TENTH GRADE STUDENTS OF SMAN 1 KOTA JAMBI - Monalisa; Adawiyah, Rabiatul (JR-ELT (Journal of Research in English Language Teaching), 2022)
This reseach have done during educational system worldwide has been affected by covid-19 pandemic, It was required the students to study at home. The researcher assumed that whatsapp as one of online leaning tool which could help the students in leaning pocess. This study aimed to find out the the effect of using WhatsApp as a learning tool on student’s writing Ability at Ma Laboratorium Kota Jambi and to find out the significant difference of students’ writing those taught using whatsapp and who taught using zoom. This research was quantitative research and it was conducted by using quasy-experimental design. Subject of this research was 34 students. The result of the analysis indicated that the mean of post-test score (69.05) was higher than the mean of pre-test score (55.97) so that Ha was accepted. It means there was significant effect and significant difference of students‘writing skill after giving treatment. Next, the researcher had computed that the score of t count> t table(2.652>2.037) and the result of paired sample T test is 2–tailed<0,05( 0.012 < 0.05),. So, Ha table was accepted. It means, there was significant effect and significant difference using WhatsApp as a learning tool onstudents writing skill.